WEAR PERFORMANCE OF DUPLEX TREATED LOW ALLOYED STEEL AGAINST WOOD (BEECH)AS STATIC PARTNER - Beliardouh, N. E.; Nouveau, C.; Kaleli, H. (SCIBULCOM LTD, 2014)
The sliding tribological behaviour of Cr-(WC-Co) coating against wood (beech) as counterpart was investigated using a duplex treatment of low carbon steel(DIN 18CrMo4). The duplex treatment consists of LPC (low pressure carburising) + R.F magnetron co-sputtering of Cr and WC-Co. Pin-on-disk configurations in dry condition wear tests were performed. The wear scars of the coatings were evaluated using optical profilometry, scanning electron microscopy (SEM/EDS) and the wear mechanisms were consequently discussed. The aim of this work is to study wear mechanisms on the wood pin/disc couple. It was concluded that best behaviour was observed in the case of higher Cr content coating.
Keywords: duplex treatment; Cr-(WC-Co) coating; wood; wear; MULTILAYER COATINGS; TOOLS; Engineering